Alterations of the Gut Microbiota in Patients With Coronavirus Disease 2019 or H1N1 Influenza. (4th June 2020) - Gu, Silan; Chen, Yanfei; Wu, Zhengjie; Chen, Yunbo; Gao, Hainv; Lv, Longxian; Guo, Feifei; Zhang, Xuewu; Luo, Rui; Huang, Chenjie; Lu, Haifeng; Zheng, Beiwen; et al.
Abstract: Background: Coronavirus disease 2019 (COVID-19) is an emerging serious global health problem. Gastrointestinal symptoms are common in COVID-19 patients, and severe acute respiratory syndrome coronavirus 2 RNA has been detected in stool specimens. However, the relationship between the gut microbiome and disease remains to be established. Methods: We conducted a cross-sectional study of 30 patients with COVID-19, 24 patients with influenza A(H1N1), and 30 matched healthy controls (HCs) to identify differences in the gut microbiota by 16S ribosomal RNA gene V3–V4 region sequencing. Results: Compared with HCs, COVID-19 patients had significantly reduced bacterial diversity; a significantly higher relative abundance of opportunistic pathogens, such as Streptococcus, Rothia, Veillonella, and Actinomyces ; and a lower relative abundance of beneficial symbionts. Five biomarkers showed high accuracy for distinguishing COVID-19 patients from HCs with an area under the curve (AUC) up to 0.89. Patients with H1N1 displayed lower diversity and different overall microbial composition compared with COVID-19 patients. Seven biomarkers were selected to distinguish the 2 cohorts (AUC = 0.94). Conclusions: The gut microbial signature of patients with COVID-19 was different from that of H1N1 patients and HCs. Our study suggests the potential value of the gut microbiota as a diagnostic biomarker and therapeutic target for COVID-19, but further validation is needed. Abstract : In this cross-sectional study, we identified specific signatures of the fecal microbiota in COVID-19 patients, H1N1 patients, and healthy controls in a Chinese population by high-throughput 16S rRNA gene sequencing, to provide a theoretical basis for intestinal microbial intervention.